2018
DOI: 10.3389/fpsyt.2018.00464
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen in the Treatment of Patients With Alcohol Use Disorder and Other Mental Health Disorders

Abstract: A limited number of medications are approved to treat Alcohol Use Disorder (AUD). Furthermore, the magnitude of their therapeutic effect is relatively modest, suggesting the potential for subtypes of patients who respond to a specific medication. The use of these medications is also limited in clinical practice by a series of contraindications such as medical comorbidities and/or concurrent use of other medications. In recent years, animal and human studies have been conducted to evaluate the efficacy of baclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Market authorization of RS(±)‐Baclofen has been decided in France by the National Agency for the Safety of Medicines (ANSM) in October 2018 with the maximum dose requirement of 80 mg per day and use after failure of other treatments. However, the international debate about its benefit/risk balance is still open as well as some questions about the great variability in the clinical response and the lack of a dose response 50 . Further studies are thus required in order to better understand the reason of the observed variability 16 …”
Section: Discussionmentioning
confidence: 99%
“…Market authorization of RS(±)‐Baclofen has been decided in France by the National Agency for the Safety of Medicines (ANSM) in October 2018 with the maximum dose requirement of 80 mg per day and use after failure of other treatments. However, the international debate about its benefit/risk balance is still open as well as some questions about the great variability in the clinical response and the lack of a dose response 50 . Further studies are thus required in order to better understand the reason of the observed variability 16 …”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analysis performed by Foulds et al 101 involved 11 studies concluded that the pooled effect size of change scores of depression scales was significant (SMD 0.25, 0.06‐0.44) only among studies concerned independent depression and was insignificant across all studies. A more recent meta‐analysis 102 included 14 studies indicated that antidepressants were significantly better than placebo on reducing the endpoint scores of interviewer‐rated depression scales (SMD −0.27, −0.49 to −0.04). Our findings were consistent with the latter one and also indicated that non‐antidepressants revealed no benefit to depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…First, contrary to the preclinical data, the clinical literature is overall conflicting, as evidenced by meta-analysis and systemic reviews aimed at examining the efficacy of baclofen for AUD treatment. These have yielded mixed results, but they were completed before these two recent RCTs ( Leggio et al ., 2010 ; Agabio and Leggio, 2018 ; Minozzi et al ., 2018 ; Palpacuer et al ., 2018 ). Consequently, in 2018, a panel of international experts met in Cagliari and reached a consensus statement that concluded that, ‘baclofen remains a promising pharmacotherapy for AUD, however, baclofen’s superiority versus placebo has not been established’.…”
Section: What Is Wrong With Baclofen Then?mentioning
confidence: 99%